Bipartite Coverings and the Chromatic Number - Mubayi, Dhruv; Vishwanathan, Sundar (The Electronic Journal of Combinatorics, 2009)
Consider a graph $G$ with chromatic number $k$ and a collection of complete bipartite graphs, or bicliques, that cover the edges of $G$. We prove the following two results: $\bullet$ If the bipartite graphs form a partition of the edges of $G$, then their number is at least $2^{\sqrt{\log_2 k}}$. This is the first improvement of the easy lower bound of $\log_2 k$, while the Alon-Saks-Seymour conjecture states that this can be improved to $k-1$. $\bullet$ The sum of the orders of the bipartite graphs in the cover is at least $(1-o(1))k\log_2 k$. This generalizes, in asymptotic form, a result of Katona and Szemerédi who proved that the minimum is $k\log_2 k$ when $G$ is a clique.